Концепция белорусского транспортного права - Sihayeva, Татьяна (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The article is devoted to the definition of the concept and place of transport law in the Belarusian legal system. It describes the discussion that takes place in the legal literature regarding the concept and place of transport law in the legal system, and modern approaches to the concept of the branch of law and the criteria for its definition in legal theory. On this basis, the author gives her own justification for the concept of Belarusian transport law as a branch of law
Keywords: transport law, subject of transport law, method of transport law, principles of transport law, transportation